2020
DOI: 10.1002/adfm.201909083
|View full text |Cite
|
Sign up to set email alerts
|

Cell and Tissue Instructive Materials for Central Nervous System Repair

Abstract: Neurodegenerative disorders and traumatic events affecting the central nervous system (CNS) represent one of the main health problems nowadays. The level of disability and impairment of these patients is very high, both at physiological and psychological level, drastically altering a person's lifestyle. The fact that CNS tissue has a limited capacity of regeneration has hampered the development of possible therapies to these conditions. The specificity of each disease also increases the complexity of creating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 252 publications
(430 reference statements)
0
13
0
Order By: Relevance
“…Addressing the above problems, one promising approach is to use scaffold materials to generate favorable microenvironments during stem cell implantation (13)(14)(15)(16). These scaffolds can help generate three-dimensional (3D) stem cell assembly, mitigate local inflammation, and establish favorable cell-extracellular matrix (ECM) interactions, typically mediated through focal adhesion kinase (FAK) signaling, which critically regulates neurogenesis and axon elongation (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the above problems, one promising approach is to use scaffold materials to generate favorable microenvironments during stem cell implantation (13)(14)(15)(16). These scaffolds can help generate three-dimensional (3D) stem cell assembly, mitigate local inflammation, and establish favorable cell-extracellular matrix (ECM) interactions, typically mediated through focal adhesion kinase (FAK) signaling, which critically regulates neurogenesis and axon elongation (17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular chemical formula of aspirin is C9H8O4, the molecular structure formula is CH3COO-C6H4COOH, and the molecular relative mass is 180. 16.…”
Section: Methodsmentioning
confidence: 99%
“…Floium ginkgo extract and tertram ethypyrazine sodium chloride injection contain ginkgo biloba extract and ligustrazine phosphate, which is a compound preparation. This study observed the effect of floium ginkgo extract and tertram ethypyrazine sodium chloride injection in the treatment of cerebral infarction (13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In order to uncover disease mechanisms and develop therapeutic strategies for brain damages and related neurological diseases, developing efficient neural regeneration models is significant and urgent. [ 1–5 ] As developed neural cells are no longer regenerative and proliferative cells, it is necessary to develop an induced cell line for neural regeneration. Induced pluripotent stem cells (IPS cells) are frequently used while obviating the necessity to obtain the tissue from the human brain or take the ethical issues destroying embryos.…”
Section: Introductionmentioning
confidence: 99%